The spectacular now [videorecording (DVD)] - Teller, Miles; Woodley, Shailene; Larson, Brie, 1989-; Tharp, Tim, 1957-
While Aimee dreams of the future, Sutter lives in the now, and yet somehow, they're drawn together. What starts as an unlikely romance becomes a sharp-eyed, straight-up snapshot of the heady confusion and haunting passion of youth.